1996
DOI: 10.1111/j.1442-9993.1996.tb00633.x
|View full text |Cite
|
Sign up to set email alerts
|

Foraging strategies in orb‐spinning spiders: Ambient light and silk decorations in Argiope aetherea Walckenaer (Araneae: Araneoidea)

Abstract: Many species of orb-spinning spiders construct silk decorations within the structure of the orb-web. The evolutionary significance of these decorations is poorly understood, but the silk decorations of many species reflect UV light, suggesting that they may function to attract insects. In these species, relatively more silk decoration may be required under dimmer light conditions in order to maintain a constant UV-reflecting signal, and hence level of insect attraction. We investigated experimentally whether t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
38
0

Year Published

1999
1999
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(39 citation statements)
references
References 15 publications
1
38
0
Order By: Relevance
“…Building stabilimenta may attract more prey, thus increasing foraging e¤ciency (Craig & Bernard 1990;Elgar et al 1996;Tso 1996Tso , 1998Watanabe 1999), or reduce the risk of predation (Robinson & Robinson 1970;Eisner & Nowicki 1983;Blackledge 1998a,b;Blackledge & Wenzel 1999). To increase their foraging success by building stabilimenta to attract prey and, at the same time, reduce the risk of predation, spiders must have strategies to balance the trade-o¡.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Building stabilimenta may attract more prey, thus increasing foraging e¤ciency (Craig & Bernard 1990;Elgar et al 1996;Tso 1996Tso , 1998Watanabe 1999), or reduce the risk of predation (Robinson & Robinson 1970;Eisner & Nowicki 1983;Blackledge 1998a,b;Blackledge & Wenzel 1999). To increase their foraging success by building stabilimenta to attract prey and, at the same time, reduce the risk of predation, spiders must have strategies to balance the trade-o¡.…”
Section: Discussionmentioning
confidence: 99%
“…Why these spiders, but not others, include stabilimenta in their webs has been debated for more than a century (Simon 1895). Although many functional hypotheses have been proposed for silk stabilimenta, the most recent and plausible, but also contentious, hypotheses are the prey-attraction hypothesis (Craig & Bernard 1990;Elgar et al 1996;Tso 1996Tso , 1998Watanabe 1999) and the predator-defence hypothesis (Horton 1980;Eisner & Nowicki 1983;Schoener & Spiller 1992;Kerr 1993;Blackledge 1998a;Blackledge & Wenzel 1999). Interestingly, both hypotheses have used the fact that stabilimenta have a bright re£ectance across wavelengths of light visible to some animals, including ultraviolet (UV) light (Craig & Bernard 1990), to argue that stabilimenta act as visual signals that make webs more conspicuous either to prey or to predators.…”
Section: Introductionmentioning
confidence: 99%
“…After removing the front and back covers from the stabilimentum decoration on the web of the wasp spider, Argiope bruennichi, actually increased the foraging success, because the web decorations reflected UV light similar to that of UV-reflecting flowers and thus, attracted insect pollinators seeking flower nectar (Kim et al 2012). The results of several studies done on the Araneid genus Argiope have offered the support for the prey-attraction hypothesis: A. trifasciata (Tso 1996), A. aetherea (Elgar et al 1996), A. appensa (Hauber 1998), A. aurantia (Tso 1998), A. keyserlingi (Herberstein 2000, Bruce et al 2001, A. versicolor (Li 2005), and A. savignyi (Gálvez 2009). …”
Section: Web Measurementsmentioning
confidence: 66%
“…However, recent research has revealed that web-building spiders adjust their foraging behaviour according to local conditions by modifying the architecture and size of the web (e.g. Elgar et al 1996;Herberstein et al 1999) and their decisions on whether to capture or leave prey items (e.g. Herberstein et al 1998).…”
Section: Introductionmentioning
confidence: 99%